IceCube High Energy Starting Events at 7.5 Years -- New Measurements of Flux and Flavor - Stachurska, Juliana (Deutsches Elektronen-Synchrotron, DESY, Hamburg, 2019)
8th Very Large Volume Neutrino Telescope Workshop, Dubna, Russia, 2 Oct 2018 - 4 Oct 2018; The European physical journal / Web of Conferences Web of Conferences : proceedings proceedings 207, 02005 - (2019). doi:10.1051/epjconf/201920702005 : The IceCube Neutrino Observatory at the South Pole, which detects Cherenkov light from charged particles produced in neutrino interactions, firmly established the existence of an astrophysical high-energy neutrino component. Here I present IceCube’s High-Energy Starting Event sample and the new results obtained with a livetime of about 7.5 years. I will focus on the new measurement of the flavor composition performed using this sample. IceCube is directly sensitive to each neutrino flavor via the single cascade, track and double cascade event topologies, the latter being the topology produced in tauneutrino interactions above an energy threshold of ~100 TeV. A measurement of the flavor ratio on Earth can provide important constraints on sources and production mechanisms within the standard model, and also constrain various beyond-standard-model processes. : Published by EDP Sciences, Les Ulis